A Critical Study on Group Key Management Protocols and Security Aspects For Non-Networks - Rituraj Jain; Manish Varshney (Journal of Applied Engineering and Technological Science (JAETS), 2023)
The rise in internet usage and advanced communication systems has led to an increase in security issues. The need for more robust and flexible secure communication has led to the introduction of mobile non-network multicast communication systems like MANET or VANET. Multicasting is increasingly being used for group-oriented applications such as video conferencing, interactive games, TV over Internet, e-learning, etc. To address the security concerns, this paper highlighted the confidentiality, authentication, and access control for non-network multicast communication systems like MANET or VANET.  For this, paper explores the group key management protocols. The paper concluded that centralized and asymmetric group key management protocol (GKMP) is most effective for designing secure, and efficient communication models for non-networks. The key findings of the paper are that in group key management protocols (GKMPs) for multicast communication systems adoption of asymmetric GKMPs provides better security, and reduces computational overhead. Therefore, this paper help to improve the robustness and security of multicast communication systems and meet the growing demands of group-oriented applications over the internet.